2020
DOI: 10.1021/acs.jpcc.9b10501
|View full text |Cite
|
Sign up to set email alerts
|

SERS and DFT Study of Noble-Metal-Anchored Cys-Trp/Trp-Cys Dipeptides: Influence of Main-Chain Direction and Terminal Modifications

Abstract: Tiny changes in the covalent structure of a noble-metal-anchored peptide may affect its surface-enhanced Raman scattering (SERS) signature. While SERS spectra of Cys-Trp peptides are dominated by the bands arising from the aromatic Trp side chain, a thorough study of the impact of modifications in SERS-silent regions concerning such dipeptides was yet to be performed. Thus, here we conduct an extensive SERS study of a series of Cys- and Trp-containing dipeptides, varying both the main-chain direction (Cys-Trp/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…The reference RS and FT-IR spectra of the dried Trp solution (10 −2 M Trp/PBS, pH 3.0) are shown in Figures 4a and 5a, respectively. The proposed band assignments were based on many theoretical and experimental data from the literature on the molecular structure of Trp and Trp derivatives obtained under various conditions [42,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. As mentioned in our previous paper [28], the preparation of samples for experiments may affect the information obtained from spectral patterns (i.e., the state of the sample condition, pH of the surrounding environment).…”
Section: Spectroscopic Results Of the Surface Adsorption Geometry Of Tryptophan On Corroded 316l Stainless Steelmentioning
confidence: 99%
See 4 more Smart Citations
“…The reference RS and FT-IR spectra of the dried Trp solution (10 −2 M Trp/PBS, pH 3.0) are shown in Figures 4a and 5a, respectively. The proposed band assignments were based on many theoretical and experimental data from the literature on the molecular structure of Trp and Trp derivatives obtained under various conditions [42,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. As mentioned in our previous paper [28], the preparation of samples for experiments may affect the information obtained from spectral patterns (i.e., the state of the sample condition, pH of the surrounding environment).…”
Section: Spectroscopic Results Of the Surface Adsorption Geometry Of Tryptophan On Corroded 316l Stainless Steelmentioning
confidence: 99%
“…Based on the clear changes in the band that appear below 880 cm −1 during the adsorption process of Trp on the corroded SS surface (Figure 4b,c) with respect to the ordinary RS spectrum, it can be concluded that there are hydrogen bonding interactions between the indole ring and the metallic surface [52,53,[62][63][64]. This spectral feature, which can be assigned to the NH group deformation, exhibits a higher relative intensity, red-shift (∆υ = 3-1 cm −1 ), and substantial broadening (∆ FWHM = 10-16 cm −1 ) compared to those observed in the normal RS spectrum.…”
Section: Stainless Steelmentioning
confidence: 95%
See 3 more Smart Citations